PERBANDINGAN EFEKTIFITAS ANTARA METODE BOUNDING (DEKAPAN ) DAN STIMULUS KUTANEUS DALAM MENGURANGI RASA NYERI SUNTIKAN INTRAMUSKULER PADA BAYI - Ethyca Sari (Jurnal Keperawatan, 2014)
Pain was a sensory experience and unpleasant consequences was emocional of the actual or potencial tissue damage . A baby needs a variety of basic immunizations required for body and immune one at them given by injection intramuskulair immunization (DPT-combo). Injections intramuskulair has pain reaction that make a baby to show pain signs , to assist in reducing the pain there are various treatments to do include bounding attachment and cutaneous stimulus, two second act at them has a good effectiveness to relieve pain due to injection intramuskulair in infants. bounding attachment (arms) psychological help your baby feel comfortable, safe in the arms of a mother while the cutaneous stimulus help the baby feel caressed by the gentle caress and touch it to make baby .This research using analytic study designs with an experimental method with a one shot case study approach and using sampling techniques with systematic random sampling, test results with the value t 2 free samples p value <0.05 then result shows that the response changes p = (0.000) pain in the boundingattachmentrata average 2.60 (1.06) differs from the change in pain response cutaneous stimulation in the group average of 7.53 (1:06) 2 free samples and for t test with the value <0.005 then the results show that there was a change when p = (0.000) minutes, the time the group bounding the average attachment 4.20 (0 , 77) in contrast to the time change in the group of cutaneous stimulation on average 9:26 (1:33), so we can conclude that there was difference in effectiveness between the bounding attachment and cutaneous stimulation in reducing pain on injection intramuskulai infants aged 2 months at the Sawahan health center.